Deixis Analysis on Article in CNN International - Tauchid, Ahmad; Ardeliya, Maya; Syafitri, Nurul Intan (English Education and Literature Journal (E-Jou), 2022)
Each language, including English, uses deixis differently due to various distinct settings, such as grammatical restrictions and cultural or customary backgrounds in society. Descriptive qualitative research is the method used to analyze the data. As data-gathering instruments, human instruments and text analysis were used. All of which are used in written form to refer to the speaker, recipients, and references who are not speakers or recipients. According to the research, the personal pronoun deixis is most commonly used in the human subject's second, third, and possessive plural forms. Additionally, deixis with a temporal focus is used in CNN International articles as speech moments, and there are two different times: the "coding" and "receiving" times (the time of recovering information by the listener who is informed). Keywords: CNN International, Deixis, Pragmatics